Communication ethics in Audit (Audit Financiar, 2018)

(untitled)
Business Ethics is a requirement but also a sine qua non criterion for the success of the auditor`s professional work with implications, in particular, on the future of the profession. In depth, communication ethics refers to the fulfilment and evaluation of the moral norm in all aspects and manifestations of the communicative interaction. The consequences of a non-ethical communication, which doesn’t consider the moral norm, will have medium and long term effects for both the auditor and the audited company, and outside the company may negatively impact a large number of stakeholders (management, employee’s families, state, customers, etc.).